2017
DOI: 10.1016/j.jacc.2017.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Underuse of Prevention and Lifestyle Counseling in Patients With Peripheral Artery Disease

Abstract: Background Little is known about patterns of medication use and lifestyle counseling in patients with peripheral artery disease (PAD) in the United States. Objective We sought to evaluate trends in both medical therapy and lifestyle counseling for PAD patients in the United States from 2005 through 2012. Methods Data from 1,982 outpatient visits among patients with PAD were obtained from the National Ambulatory Medical Care Survey and National Hospital Ambulatory Medical Care Survey, a nationally represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(99 citation statements)
references
References 21 publications
3
91
1
4
Order By: Relevance
“…This finding emphasises the importance of optimising treatment in the general peripheral artery disease population. 4,25,26 Consistent benefits in the reduction of major adverse cardiovascular events and major adverse limb events occurred with combination of rivaroxaban 2·5 mg plus aspirin compared with aspirin alone but did not occur to the same extent with the rivaroxaban 5 mg twice a day regimen. These results are also consistent with the results of the overall trial, which have been reported separately.…”
Section: Discussionmentioning
confidence: 98%
“…This finding emphasises the importance of optimising treatment in the general peripheral artery disease population. 4,25,26 Consistent benefits in the reduction of major adverse cardiovascular events and major adverse limb events occurred with combination of rivaroxaban 2·5 mg plus aspirin compared with aspirin alone but did not occur to the same extent with the rivaroxaban 5 mg twice a day regimen. These results are also consistent with the results of the overall trial, which have been reported separately.…”
Section: Discussionmentioning
confidence: 98%
“…According to national surveys of ambulatory care practices, adherence to guideline-directed medical therapy in patients with PAD lags behind that of CHD, whereas a co-diagnosis of CHD increases the odds of proper PAD treatment [3]. Adherence to CHD risk factor modification has also been found to be suboptimal in patients with diabetes [5].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes severity was stratified by [1] no use of medications (e.g. diet controlled) [2], use of oral glucose-lowering agents only, or [3] use of insulin with or without the use of oral glucose-lowering agents. Coronary heart disease (CHD) was defined as prior myocardial infarction or prior coronary revascularization (coronary artery bypass, angioplasty, or percutaneous coronary intervention).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported underutilization of established risk‐reduction therapies such as statins for peripheral artery disease relative to coronary artery disease,6, 7, 8 which may lead to poor cardiovascular and limb outcomes 9. Nevertheless, few data exist on the utilization of statin therapy among patients with carotid artery disease.…”
Section: Introductionmentioning
confidence: 99%